Role of ectodysplasin signalling in middle ear and nasal pathology in rat and mouse models of hypohidrotic ectodermal dysplasia - Jorge del-Pozo; Neil MacIntyre; Ali Azar; Denis Headon; Pascal Schneider; Michael Cheeseman (The Company of Biologists, 2019)
Patients with mutations in the ectodysplasin receptor signalling pathway genes - the X-linked ligand ectodysplasin-A (EDA), the receptor EDAR or the receptor adapter EDARADD - have hypohidrotic ectodermal dysplasia (HED). In addition to having impaired development of teeth, hair, eccrine sweat glands, and salivary and mammary glands, HED patients have ear, nose and throat disease. The mouse strains Tabby (EdaTa) and downless (Edardl-J/dl-J) have rhinitis and otitis media due to loss of submucosal glands in the upper airway. We report that prenatal correction of EDAR signalling in EdaTa mice with the agonist anti-EDAR antibody rescues the auditory-tube submucosal glands and prevents otitis media, rhinitis and nasopharyngitis. The sparse- and wavy-haired (swh) rat strain carries a mutation in the Edaradd gene and has similar cutaneous HED phenotypes to mouse models. We report that auditory-tube submucosal glands are smaller in the homozygous mutant Edaraddswh/swh than those in unaffected heterozygous Edaraddswh/+ rats, and that this predisposes them to otitis media. Furthermore, the pathogenesis of otitis media in the rat HED model differs from that in mice, as otitis media is the primary pathology, and rhinitis is a later-onset phenotype. These findings in rodent HED models imply that hypomorphic as well as null mutations in EDAR signalling pathway genes may predispose to otitis media in humans. In addition, this work suggests that the recent successful prenatal treatment of X-linked HED (XLHED) in humans may also prevent ear, nose and throat disease, and provides diagnostic criteria that distinguish HED-associated otitis media from chronic otitis media with effusion, which is common in children.